2019
DOI: 10.1002/ajim.23039
|View full text |Cite
|
Sign up to set email alerts
|

Hired Latinx child farm labor in North Carolina: The demand‐support‐control model applied to a vulnerable worker population

Abstract: Background: US government child labor policies allow children as young as age 10 to be hired as workers on farms not operated by family members. Children may face substantial health risks in an industry known for high worker morbidity and mortality rates, due to high demands for productivity, and low control and little support because of the organization of the workplace. This paper examines how child farmworkers in North Carolina experience their work situation. Methods: In-depth interviews conducted in 2016 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 24 publications
(44 citation statements)
references
References 47 publications
1
42
1
Order By: Relevance
“…These statistical patterns reflect the qualitative analyses of Quandt et al 19 on the organization of work and of Arcury et al 18 on work safety culture among Latinx child farmworkers. In in‐depth interviews, the Latinx child farmworkers described the extensive work demands that they experienced, including the need to work quickly and take risks by working in excessive heat, lifting heavy loads, and working with machinery 19 . They also felt that they had little control over their work environment, laboring with the fear of being fired, having wages withheld, and being yelled at.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…These statistical patterns reflect the qualitative analyses of Quandt et al 19 on the organization of work and of Arcury et al 18 on work safety culture among Latinx child farmworkers. In in‐depth interviews, the Latinx child farmworkers described the extensive work demands that they experienced, including the need to work quickly and take risks by working in excessive heat, lifting heavy loads, and working with machinery 19 . They also felt that they had little control over their work environment, laboring with the fear of being fired, having wages withheld, and being yelled at.…”
Section: Discussionsupporting
confidence: 69%
“…They have more unsafe work attitudes, and they have a lower perceived work safety climate, with more feeling that their supervisor is only concerned with getting the job done fast and cheap. Qualitative analysis indicates that child farmworkers get some work support from parents, 19 and that, in addition to providing much of their safety training, adult relatives emphasize the need to work safely 17 . The role of working with family members in work safety needs to be examined further.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…33,36 Factors outside the control of child farmworkers such as the intensity and pace of farm work tasks, long work hours, limited control over their work environment, and lack of regulatory frameworks in agriculture increase their risk of HRI. 15,[37][38][39] Summers are extremely hot and humid in North Carolina (Table 1). 40 The findings from a recent study of Latinx child farmworkers in North Carolina indicate that children experience considerable exposure to working in peak summer heat.…”
Section: Child Farmworkers and Exposure To Heatmentioning
confidence: 99%
“…41 Farm work is organized in a way that further exacerbates children's vulnerability due to the crew leader system and children's unique developmental characteristics, which may make them reticent to speak out against unsafe conditions. 37 Many farmworkers are paid piece rate wages, which incentivizes productivity and can make workers less likely to take breaks and more likely to work at an unsafe pace. [42][43][44][45][46] Previous research with Latinx child farmworkers in North Carolina found that they perceived low levels of work safety culture and climate in farm work.…”
Section: Child Farmworkers and Exposure To Heatmentioning
confidence: 99%